2022
DOI: 10.48550/arxiv.2202.13379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards early dark energy and $n_s$=1 with Planck, ACT and SPT

Jun-Qian Jiang,
Yun-Song Piao

Abstract: We investigate the constraints on early dark energy (EDE) by combining the most recent CMB observations available, ACT DR4, SPT-3G, and Planck2018 ( TT,max = 1000) data. This combined CMB dataset favors non-zero EDE fractions and large Hubble constants, i.e. H 0 = 72.3(73.4) +2.2 −1.7 and 73.32(72.98) +0.68 −0.95 km/s/Mpc for axion-like EDE and AdS-EDE, respectively. The inclusion of BAO+Pantheon data has little efffect on the results. The axion-like EDE can fit the data significantly better (∆χ 2 −10) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Let us briefly discuss the main results of the original EDE proposal resolving the Hubble tension [566,567,579], its limitations [385,490,547,587,588], and the recent hint for EDE in ACT data [589][590][591] (which is also consistent with SPT data [591][592][593]). The model proposes a new scalar field φ with a potential of the form…”
Section: Early Dark Energymentioning
confidence: 70%
See 2 more Smart Citations
“…Let us briefly discuss the main results of the original EDE proposal resolving the Hubble tension [566,567,579], its limitations [385,490,547,587,588], and the recent hint for EDE in ACT data [589][590][591] (which is also consistent with SPT data [591][592][593]). The model proposes a new scalar field φ with a potential of the form…”
Section: Early Dark Energymentioning
confidence: 70%
“…Recently, the EDE model has been confronted with ACT data leading to a (perhaps surprising) preference for EDE at ∼ 2σ from ACT alone. Once combined with WMAP (or Planck TT at < 650), BAO, and Pantheon data, the presence of EDE is favored at 3σ, with f EDE (z c ) 0.16 +0.05 −0.09 (note that posteriors are non-Gaussian) and H 0 (73.4 ± 3) km s −1 Mpc −1 , without including any information from SH0ES [589][590][591]. The significance of the preference and the parameter estimation remain consistent with this picture even after the inclusion of SPT-3G [591][592][593] and Planck polarization data [590,593].…”
Section: Early Dark Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results highlight the extremely important role of FS measurements in the era of precision cosmology, particularly in further sharpening constraints on models beyond ΛCDM: for instance, a recently well-documented example in this context is that of the early dark energy model [249,250,[338][339][340][341][342][343][344][345]. Furthermore, contrary to what occurs within the ΛCDM model and simple extensions thereof, we have demonstrated that constraints obtained by combining CMB and FS data are tighter than those obtained by combining CMB and BAO mea-surements, suggesting that in the context of IDE models there is significant information contained in the broadband of the power spectrum.…”
Section: Discussionmentioning
confidence: 70%
“…EDEs with scaling solutions in the matter-and radiation-dominated eras [901][902][903][904] are not capable of relieving the H 0 tension in a significant way [836,905] Planck high-temperature data restricts that preference to below the 2σ level. The inclusion of Planck polarization data strengthen the preference [911], while SPT-3G data play little role in constraining the EDE model [911][912][913]. Additionally, EDE models tend to slightly increase the S 8 tensions [853,914] and can be constrained with the full shape of the galaxy power spectrum [915,916], although current data are inconclusive [887,[917][918][919].…”
Section: Ingmentioning
confidence: 85%